PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN MANUFAKTUR DI INDONESIA YANG TERDAFTAR DI BEI - Yuniarti, Mustika; Syaichu, Muhamad (Faculty of Economics and Business Diponegoro University, 2018)
This research aims to analyze the influence of Good Corporate Governance to the performance of manufacturing companies. The variables tested in this research are board of director (DEDIR), board of commisioner (DEKOM), independent commissioner (KOMIND), concentrated ownership (CONSOWN), institutional ownership (INSTOWN), and managerial managerial (MANOWN) to ROA. In addition, in this study also use control variables size and leverage. Research objects for this study are manufacturing companies in Indonesia listed on BEI (Bursa Efek Indonesia). This research was conducted by purposive sampling method at manufacturing companies in Indonesia which listed on BEI from 2012 until 2016. The number of samples obtained by 34 manufacturing companies. Secondary data used in this study is from annual financial report data downloaded through IDX official website and official website of each company. The method of analysis used in this study is multiple linear regression analysis with 5% significance level and previously performed classical assumption test that include normality test, multicolinearity test, autocorrelation test, and heteroscedasticity test. The results of this research indicate that board of directors (DEDIR), board of commissioners (DEKOM), independent commissioners (KOMIND), concentrated ownership (CONSOWN), and managerial ownership (MANOWN) have no significant effect on ROA. While institutional ownership (INSTOWN) shows a significant negative effect on ROA. The control variable size does not show any significant effect on ROA. While leverage has a significant negative effect on ROA. Based on the result of determination coefficient board of directors (DEDIR), board of commissioner (DEKOM), independent commissioner (KOMIND), concentrated ownership (CONSOWN), institutional ownership (INSTOWN), managerial ownership (MANOWN), size and leverage have influence of 12.6% against ROA. While the remaining of 87.4% influenced by other variables that are not used in this study.